Posted by andre on Tuesday, July 19, 2011 at 8:47am.
multiply each term by 2
x - 12 = 10
take it from here.
Algebra1 - I want to know if I got this problem right. 2x-4¡Ü4x-3 2x-...
algebra1 - 1/2x-6=5
algebra1 - 4(x+3)=2(x-6) 4x+12=2x-12 2x+12=-12 2x=-24 x=-12 is this textbook ...
Algebra1 - if x-3y=8 and y=2x+1, then x= ???
Algebra1 - 3x/4 - 2x/5 + x/2
Algebra1 - 2x-7+x=11-5x+6
algebra1 - (2x^2+3x-15) divided by (x-3)
algebra1 - y=the negative square root of 2x
algebra1 - wihtout graphing, is this system independent, dependent, or ...
algebra1 - I am confused the question says: Find f(-2) given that f(x)=4x^2-2x-...
For Further Reading